2020
DOI: 10.1097/icl.0000000000000680
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Evidence-Based Treatments for Meibomian Gland Dysfunction

Abstract: Objectives: To evaluate recent studies on available therapies for meibomian gland dysfunction (MGD). Methods: A literature search on recent publications, within the last five years, concerning treatment options for MGD was performed. Results: A total of 35 articles were reviewed after curation by the authors for relevance. In general, all modalities of treatments were shown to have clinical efficacy in allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 78 publications
2
64
0
Order By: Relevance
“…In a review of eight different treatments for dry eye, meibomian gland expression and thermal pulsation appeared to be effective in treating dry eye symptoms; further, Vegunta et al showed that patients who failed to improve with thermal pulsation treatment alone improved significantly with IPL treatment. 23,24 The high-intensity red (560-580 nm) to infrared (580-1200 nm) wavelengths of light in our BBL protocol may also be improving the disease by reducing harmful bacteria and Demodex mite infestation. 12,13 This technology, however, has the capacity to harm.…”
Section: Figmentioning
confidence: 99%
“…In a review of eight different treatments for dry eye, meibomian gland expression and thermal pulsation appeared to be effective in treating dry eye symptoms; further, Vegunta et al showed that patients who failed to improve with thermal pulsation treatment alone improved significantly with IPL treatment. 23,24 The high-intensity red (560-580 nm) to infrared (580-1200 nm) wavelengths of light in our BBL protocol may also be improving the disease by reducing harmful bacteria and Demodex mite infestation. 12,13 This technology, however, has the capacity to harm.…”
Section: Figmentioning
confidence: 99%
“…A longer treatment period of 2-3 months would provide a better prospective on the signs and symptoms of DE. Additionally, dose and duration of IPL treatment required for CLDE has not been assessed before [48,49], therefore future study will explore the optimal dose and duration of IPL treatment required.…”
Section: Discussionmentioning
confidence: 99%
“…24 MGP is also mentioned in recent reviews looking at the treatment of MGD, with one published as recently as January, 2020. 19,32,33,37 Five retrospective studies were included in this review. 22,23,25,26,36 Four of these five were conducted by the same first author using his past patients' charts.…”
Section: 1mentioning
confidence: 99%